Le professeur d'université et la notion de salarié du Code du travail du Québec - Chalifoux, Denise (Les Cahiers de droit, 1984)
The split decision of the Supreme Court of the United States in the Yeshiva University case in 1980 highlighted the difficulties inherent in appliying American labour laws to the university milieu. This paper considers whether a similar problem exists in Quebec today in regard to the notion of employee found in the Quebec Labour Code and the functions of a university professor. The author first characterizes a professor's work on the basis of the role and responsabilities assigned to him by the different constitutive laws of the Quebec universities in order to establish, in a second section, to what extent this type of occupation is compatible or not with the carefully analysed notion of employee as it is found in the Quebec Labour Code. While this study does not support the conclusion that the associations of university professors should not have been accredited in the first place, nor that decisions to that effect could have been or still could be reversed as in the case of Yeshiva, nor even that these accreditations were detrimental to the university milieu, it does show that the provisions of the Quebec Labour Code inadequately reflect the realities of the Quebec university milieu. It points out the direction possible changes should take to correct this problem.